The Effect of High Carbohydrate and Fat Consumption on Growth Hormone Response to Physical Activity in Children - Shirin Zilaei Bouri; Hossein Khalafian; Noshin Andishi (Islamic Azad University, 2016)
Introduction: present study aimed to investigate the effect of type of food on growth hormone concentrations in response to physical activity in children. Methods: 25 boys (aged 9-14) with complete physical health were randomly divided into three groups, including high carbohydrate (65% carbohydrate, HC), high fat (50% fat, HF), and Normal (N) diet. Physical activity included 10 cycles of 6 seconds sprint running for 20 minutes. Blood was taken in the fasting state, 45 minutes after diet, and 15 minutes after physical activity. Repeated measure ANOVA, factorial analysis of variance and Tukey's post hoc test at significant level of 0.05 were used to analyze the data. Results: After breakfast, the growth hormone decreased in HC and HF groups. In the HF group, the increase in growth hormone after activity was significant compared to the fasting state (P = 0.01) and post-breakfast state (P = 0.03). The increase after activity was significant in comparison with the post-breakfast state (P = 0.03) in the HF group. In the N group, the growth hormone increased after breakfast (P = 0.03) and activity (P = 0.04) compared to the fasting state. Conclusion: Consumption of food with carbohydrates and lipids reduces the growth hormone secretion, but does not change the response to activity.